What drives firms' investment in climate change? Evidence from the 2022-2023 EIB Investment Survey - EUROPEAN INVESTMENT BANK (European Investment Bank, 2023)
High energy prices in Europe and uncertainty caused by the Ukraine war are testing EU firms' ability to invest in climate change measures. Europe urgently needs to embrace the transition to green energy, and firms will be called upon to play a pivotal role. By investing in climate adaptation and mitigation measures, especially energy efficiency, firms will be able to protect themselves against extreme climate events, reduce energy costs and take the actions needed to reduce carbon emissions to net-zero by 2050. The report What drives firms' investment in climate action? Evidence from 2022-2023 EIB Investment Survey uses data collected from firms to provide insight on how businesses are responding to the energy crisis and the fast-changing business environment. Some important takeaways: 82% of EU firms say energy costs are an obstacle to investment. 42% of firms in Western and Northern Europe are investing in energy efficiency, compared with only 37% of firms in Southern Europe. 57% of EU firms are concerned about the physical risks posed by climate change. A presentation of the report results - EN Country scoreboard Country scoreboard: SMEs Country scoreboard: Large Firms Country dashboards Austria Belgium Bulgaria Croatia Cyprus Czech Republic Denmark Estonia Finland France Germany Greece Hungary Ireland Italy Latvia Lithuania Luxembourg Malta Netherlands Poland Portugal Romania Slovakia Slovenia Spain Sweden